Pengaruh Leisure Satisfaction terhadap Caregiver Burden di Panti Perlindungan dan Rehabilitasi Sosial Lanjut Usia Budi Sejahtera Kalimantan Selatan - Lelana, Dian Jaya; Quarta, Dicky Listin; Fitriah, Aziza (Universitas Nurul Jadid, 2025)
Caregiver burden refers to the psychosocial strain experienced by caregivers as a result of their involvement in providing long-term care for older adults, both from a subjective and objective perspective. One factor assumed to influence the level of caregiver burden is leisure satisfaction, which reflects the positive perceptions that arise from engaging in leisure activities. The present study aims to examine whether leisure satisfaction has an effect on caregiver burden at PPRSLU Budi Sejahtera. This study employed a quantitative approach with a correlational design. A total of 40 respondents were recruited using a total sampling technique. The instruments applied were the Leisure Satisfaction Scale (LSS) and the Zarit Burden Interview. Simple linear regression analysis was conducted to assess the influence of leisure satisfaction (independent variable) on caregiver burden (dependent variable). The linearity test yielded a significance value of p = 0.771 (p > 0.05), indicating that leisure satisfaction did not have a significant effect on caregiver burden. Therefore, the proposed hypothesis was not supported. In conclusion, leisure satisfaction does not significantly affect caregiver burden. This study contributes to the literature on caregiver burden by demonstrating that leisure satisfaction alone does not explain the strain experienced by caregivers, suggesting that other factors need to be considered in understanding caregiver burden among those caring for older adults